EVALUASI KINERJA DISTRIBUTOR PT BCD MENGGUNAKAN METODE TOPSIS BERDASARKAN JUMLAH KLAIM DISKON DAN JUMLAH TOKO - Tri Astuti, Amanda Rahma; Seputro, Dimas Nugroho Dwi (STIE Mahardhika, 2026)
This study aims to evaluate the performance of PT BCD distributors based on the intensity of discount claims and the number of stores managed. Performance evaluation was conducted using a quantitative approach by combining the Productivity Index (PI) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) methods. The PI method was used as an initial stage to measure productivity per store and filter distributors with the highest claim intensity. Based on the PI calculation results, ten distributors with the highest productivity values were obtained and further analyzed using the TOPSIS method as a multi-criteria decision-making approach. The TOPSIS method was applied through the stages of decision matrix formation, data normalization, criteria weighting, determination of positive and negative ideal solutions, distance calculation, and determination of preference values and distributor rankings. The results of the study show a difference in rankings between the PI and TOPSIS methods, indicating that distributor performance evaluation cannot be based solely on a single ratio indicator. The integration of PI and TOPSIS produces a more comprehensive and objective evaluation framework, which can be used as a basis for managerial decision-making in controlling discount claims and fostering distributor performance.